PENGARUH TEKNIK COGNITIVE RESTRUCTURING UNTUK MENINGKATKAN KONSEP DIRI KORBAN BULLYING MELALUI BIMBINGAN KELOMPOK DI SMP NEGERI 29 PEKANBARU - Fitri Rahmadani; Rosmawati Rosmawati; Zulfan Saam (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstrack: This study aims to determine the differences in self-concept of bullying victims before and after the implementation of Cognitive Restructuring techniques through group guidance and determine the effect of Cognitive Restructuring techniques to improve self-concept of bullying victims through group guidance. The study was conducted at Pekanbaru State Middle School 29 of 7 subjects with purposive sampling technique. The research design was pre-experiment with the one group pre-test post-test model. The instrument of data collection used is the self-concept measurement scale. The results showed that there were differences in self-concept of bullying victims before and after the cognitive restructuring technique was given with a significance value of 0.018 <0.05. In addition, based on the Spearman rank test it is known that there is a significant effect between the Cognitive Restructuring technique to improve the concept of bullying victims with a significance value of 0.014 <0.05. The effect of Cognitive Restructuring techniques to improve self-concept of bullying victims is 73% while 27% is influenced by other factors that come from within and from the student's environment. From the results obtained, it is recommended that educational institutions should continue to carry out activities that are able to improve students' self-concept in the teaching and learning process to encourage more positive self-development, physical, social, family, and moral-ethics.Key Words : Bullying Victims, Cognitive Restructuring Technique, Group Guidance, Self Concept.